PENGARUH PUPUK SUBSIDI DAN LUAS LAHAN TERHADAP PENDAPATAN PETANI PADI DI DUSUN AEK RAU DESA SIMANGUMBAN JULU KECAMATAN SIMANGUMBAN KABUPATEN TAPANULI UTARA - Sinaga, Intan Octavianty; Siagian, Nalom; Sinaga, Kepler (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the effect of subsidized fertilizer and land area on the income of rice farmers in Aek Rau Hamlet, Simangumban Julu Village,District Simangumban, Nort Tapanuli Regency. This type of research is associative with a quantitative approach. The population in this research is 87 rice farmers using rice farmers using the saturation point formula technique, because the population is less than 100, the number of samples in this research is taken absolutely from a population of 87 respondents. Based on the test subsilized fertilizer with tcount > ttable (4,095>1,988) with a significant level of 0,000 < 0,05, then the land area variable obtained ttable > tcount (7,840> 1,988) with a significant level of 0,000 < 0,05, thus it can be concluded that the variable subsidized fertilizer and land area partilially have a positive and significant effect on the income of rice farmers in Aek Rau Hamlet, Simangumban Village, Julu Simangumban District, Nort Tapanuli Regency. The faitung value of 30,517 is greater than Eubal’s 3,11 with 0,000 < 0,05 indicating Ho rejected and Ha accepted. So, it can be concluded that the variables of subsidized fertilizer and land area together have a positive and significant effect on the income of rice farmers in Aek Rau Hamlet, Simangumban Village, Julu, Simangumban District, North Tapanuli Regency. Coefficient of Determination (R2) = R2 X 100%, so that R2 = 0,421 or 42,1% of farmer income (dependent variable) can be explained by the variables subsidized fertilizer and land area. The remaining 57,9% is influenced by other factors not explained in this study.